Analisis Sosiologi Hukum atas Polemik dan Dampak Meningkatnya Permohonan Dispensasi Perkawinan di Jawa Timur tahun 2022 - Khaidarulloh, Khaidarulloh (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Marriage is an important institution in human social life, both in terms of religion, culture, and law. However, in some cases, there are situations where couples who want to marry must request dispensation from the applicable law, as was the case in East Java in 2022, where there was an increase in the number of applications for marriage dispensation. This study aims to analyze social and legal factors with a sociological-jurisprudence approach. The research method used is a qualitative approach using literature study techniques and relevant skunder data related to the dynamics of the marriage dispensation. The results showed that factors influencing the decision to apply for marriage dispensation include economic, cultural, religious factors, also influenced by social changes and policies related to the minimum age of marriage. The polemic regarding the marriage dispensation needs to get deeper attention, so that the judiciary and the government can determine the right policy to deal with the phenomenon.